2011
DOI: 10.1186/1756-3305-4-214
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii infection in household and stray cats in Lanzhou, northwest China

Abstract: BackgroundToxoplasma gondii is an important protozoan parasite infecting humans and almost all warm-blooded animals. As the only definitive host, cats play a crucial role in the transmission of T. gondii infection by shedding parasite oocysts in their feces. However, little information on T. gondii infection in cats was available in Lanzhou, northwest China. This study was performed to determine the seroprevalence of T. gondii infection in household and stray cats in Lanzhou, northwest China.ResultsA total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 18 publications
3
23
1
Order By: Relevance
“…The cat serological prevalences predicted by [10] agree with values observed along the urban rural gradient: when natural populations (as opposed to heterogeneous samples constituted from veterinary clinics or facilities) are considered, seroprevalences are clearly lower in urban (between 15 % to 26% [41,33,34,42,43]) than in rural areas (48% to 87.3% [44,30,45,32,42]). They also reach high values in non-anthropized areas: 51% in Kerguelen island [46].…”
Section: Variations In T Gondii Dynamics Along the Urban-rural-wild supporting
confidence: 65%
See 1 more Smart Citation
“…The cat serological prevalences predicted by [10] agree with values observed along the urban rural gradient: when natural populations (as opposed to heterogeneous samples constituted from veterinary clinics or facilities) are considered, seroprevalences are clearly lower in urban (between 15 % to 26% [41,33,34,42,43]) than in rural areas (48% to 87.3% [44,30,45,32,42]). They also reach high values in non-anthropized areas: 51% in Kerguelen island [46].…”
Section: Variations In T Gondii Dynamics Along the Urban-rural-wild supporting
confidence: 65%
“…This parameter is crucial for the transmission of T. gondii from IH to DH: combined with the prevalence in prey, it determines the risk for a cat to get infected. The importance of the predation rate is illustrated by the finding that cats with frequent outdoor access show higher predation rates [16] and higher prevalences than cats not allowed to roam [30,31,32,33,34]. The predation rate depends on the availability of rodents, i.e., on the density of rodents relative to cats, and on the availability of other food resources provided by people.…”
Section: Host Densities and Predation Rates Vary Along A Urbanizationmentioning
confidence: 99%
“…Antibodies to T. gondii were determined in cat sera by the modified agglutination test (MAT) as described previously (Wu et al 2011). In brief, sera were added to "U"-bottom 96-well microtiter plates, diluted twofold starting from 1:25 to 1:1600; the plates were shaken for 2 min and then incubated at 37°C overnight without shaking.…”
Section: Serological Examinationmentioning
confidence: 99%
“…Epidemiological data are necessary to define preventive, management, and therapeutical measures for stray, feral, and domestic cats. Although several studies have reported the T. gondii prevalence in cats in various regions in China (Dubey et al 2007;Chen et al 2011;Qian et al 2012;Wang et al 2013;Tian et al 2014), including Lanzhou (Wu et al 2011), little is known of the genotypes of T. gondii in cats in northwest China. Here, we investigated the genotypes of T. gondii in cats in northwest China for the first time.…”
Section: Introductionmentioning
confidence: 98%
“…Serum samples from Tibetan pigs were diluted twofold from 1:25 to 1:1600 and examined for T. gondii antibodies using the modified agglutination test (MAT) as described previously (Dubey and Desmonts 1987;Wu et al 2011aWu et al , 2011b. In this study, sera with MAT titers of 1:25 or higher were considered positive, because T. gondii can be isolated from naturally-infected pigs with antibody titers as low as 1:25 by MAT (Dubey et al 1995a, Dubey 1997).…”
Section: Serological Examinationmentioning
confidence: 99%